Apatinib manifests an unexpectedly favorable outcome in the management of axillary lymph node follicular dendritic cell sarcoma: a case report - Feng, Zhiying; Du, Zhonghai; Liang, Yan; Zhou, Juyue (Frontiers in Oncology, 2024)
We present a case of follicular dendritic cell sarcoma in the axillary lymph node, which unexpectedly showed favorable outcomes after the application of apatinib. Follicular Dendritic Cell Sarcoma (FDCS) exhibits a rare incidence and an unclear pathogenic mechanism, contributing to the limited breakthroughs in its treatment to date within the medical field. The current mainstream therapeutic approaches include surgery, CHOP(cyclophosphamide, doxorubicin, vincristine, prednisone), ICE(ifosfamide, carboplatin, etoposide), ABVD(doxorubicin, bleomycin, vinblastine, dacarbazine), and immune checkpoint inhibitors. A 38-year-old male patient was admitted to the hospital due to a lump in the right axilla and underwent surgical treatment. Postoperative pathology confirmed the diagnosis of follicular dendritic cell sarcoma. Two months post-surgery, he faced a recurrence, prompting a subsequent surgical intervention complemented by tumor radiofrequency ablation. Despite these interventions, the treatment response was suboptimal. Subsequently, the patient was treated with the CHOP regimen, but after two cycles, he developed bone metastasis. Due to the patient's limited financial resources and refusal of immunotherapy, we switched to a regimen of gemcitabine and docetaxel, but the disease progressed again after two cycles. A one-cycle trial of albumin-bound paclitaxel yielded unsatisfactory results. Ultimately, the patient was treated with Apatinib, achieving a 10-month progression-free survival. Due to the patient's limited financial circumstances, we, in the absence of guideline recommendations and evidence from evidence-based medicine, achieved a 10-month progression-free survival (PFS) solely based on experiential use of the anti-angiogenic drug, Apatinib. The purpose of this case report is to provide additional therapeutic options for FDCS treatment and to pave the way for exploring the mechanism of action of Apatinib in FDCS.